Tranquillity trails – design, implementation and benefits for healthy leisure. Issue 2 (3rd April 2022) - Watts, Greg; Bauer, Juergen
ABSTRACT: Tranquillity trails (TTs) are designed to provide a quiet and peaceful walk through mainly leafy lanes and roads and connect green open spaces where visitors can stop for thought and relaxation. There are numerous health benefits from being in close proximity to nature and TTs can facilitate this contact in mainly urban areas. This study involved the design of a trail in Tramore, a coastal town in south east Ireland. The trail links an old coastguard station, now converted to a cultural centre and coffee shop, with a Japanese garden. The trail includes a coastal path with fine views across a bay, wooded areas as well as leafy residential streets. The design of the trail was facilitated by the use of a previous developed tranquillity rating prediction tool (TRAPT) that involved the estimation of the level of man-made noise and the percentage of natural features in view. Participants who had completed the whole of the trail were encouraged to complete a questionnaire to gauge any benefits. As expected, it was reported that there were increased levels of relaxation and reduced stress. It was concluded that the approach can be used elsewhere to improve the well-being of residents and visitors.